2012
DOI: 10.1159/000341796
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery with or without Embolization for Intracranial Dural Arteriovenous Fistulas

Abstract: Treatment options for symptomatic dural arteriovenous fistulas (DAVFs) include surgery, embolization and stereotactic radiosurgery (SRS). We reviewed our DAVF experience at the University of Pittsburgh and assessed the role of SRS. We evaluated 40 consecutive patients who underwent Gamma Knife SRS for 44 DAVFs. Twenty-eight patients had upfront SRS before or after embolization performed at our institution, and 12 patients underwent delayed SRS for recurrent or residual DAVFs after initial embolization. The med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…Pan et al 24 reported their series of 41 patients treated by stereotactic radiosurgery for CSDF with a 90% obliteration rate. Yang and colleagues25 showed similar results in their cohort of 40 patients treated by stereotactic radiosurgery. They also found that CSDF was associated with higher rates of occlusion (p=0.012) and improvement in symptoms (p=0.010) than was transverse–sigmoid sinus fistula.…”
Section: Discussionmentioning
confidence: 69%
“…Pan et al 24 reported their series of 41 patients treated by stereotactic radiosurgery for CSDF with a 90% obliteration rate. Yang and colleagues25 showed similar results in their cohort of 40 patients treated by stereotactic radiosurgery. They also found that CSDF was associated with higher rates of occlusion (p=0.012) and improvement in symptoms (p=0.010) than was transverse–sigmoid sinus fistula.…”
Section: Discussionmentioning
confidence: 69%
“…SRS can also be a treatment option for patients in whom endovascular or open surgical treatments are deemed to carry high procedure-related risks and in patients with residual fistulas following prior treatments. SRS has shown reasonably good obliteration rates; the complete obliteration rates of DAVS after SRS was about 68% with SRS alone and 83% in SRS combined with endovascular treatment 59 60. Complication rates were very low with post-SRS hemorrhage, neurologic deficit, and mortality rates of 1.2%, 1.3%, and 0.3%, respectively 60.…”
Section: Managementmentioning
confidence: 99%
“…The therapeutic delay of stereotactic radiosurgery would be unacceptable for most patients except those with very high peri-procedural risks. Stereotactic radiosurgery may be a reasonable alternative in asymptomatic patients and those that carry a high periprocedural risk, but this has to be proven by further studies [38].…”
Section: Therapeutic Optionsmentioning
confidence: 99%